The rise of compassionate ageism: Long-term care employees’ attitudes toward aging during COVID-19 - Loy-Ashe, Tarah; Hawkins, Brent L.; Puymbroeck, Marieke Van; Lewis, Stephen T.; Hays, Antoinette M. (American Journal of Recreation Therapy, 2022)
Objectives: Research suggests that ageist beliefs and behaviors have increased since the onset of the novel coronavirus 2019 (COVID-19). Considering that COVID-19 has taken a particularly heavy toll on long-term care (LTC) residents, this study examined if LTC employee perceptions of aging were influenced by working in a LTC facility during the pandemic.Methods: Qualitative data collection included 30-minute interviews with 21 LTC employees in the Boston, Massachusetts, area including 10 nurses, three nursing assistants, four clinical coordinators, two social workers, one recreation therapist, and one registered dietitian.Results: An increase in perceptions and behaviors representative of compassionate ageism (CA) was self-reported among participants.Discussion: The current study demonstrates how an increase in CA among employees was perpetuated by the COVID-19 pandemic. Allied health and nursing professionals should be mindful of attitudes toward aging, and how health events can reinforce ageist beliefs and behaviors. Opportunities for recreation therapists to lead antiageist efforts in LTC are identified.
Keywords: COVID-19; aging; compassionate ageism; dept.hls; long-term care; peer-reviewed; recreational therapy; ⚠️ Invalid DOI